2013
DOI: 10.1371/journal.ppat.1003750
|View full text |Cite
|
Sign up to set email alerts
|

A Unique SUMO-2-Interacting Motif within LANA Is Essential for KSHV Latency

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) stabilizes hypoxia-inducible factor α (HIF-1α) during latent infection, and HIF-1α reactivates lytic replication under hypoxic stress. However, the mechanism utilized by KSHV to block lytic reactivation with the accumulation of HIF-1α in latency remains unclear. Here, we report that LANA encoded by KSHV contains a unique SUMO-interacting motif (LANASIM) which is specific for interaction with SUMO-2 and facilitates LANA SUMOylation at lysine 1140. Proteomic and co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
91
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(97 citation statements)
references
References 65 publications
(92 reference statements)
5
91
1
Order By: Relevance
“…Viruses can counteract or enhance the host's sumoylation to evade the immune response and antagonize apoptosis, while some viruses exploit the host's sumoylation machinery to sumoylate the viral components which are necessary to perform viral functions (48). It has been reported that KSHV modulates the SUMO pathway through RTA/ORF50, K-bZIP/K8, and vPK/ORF36 during lytic replication as well as LANA/ORF73 and viral IRF3 (IRF3)/K10.5/LANA-2 during latency (27,35,(49)(50)(51)(52)(53)(54)(55)(56). Our results showed that LANA bound directly to the SENP6 promoter and repressed its activity, inhibiting SENP6 expression at both the RNA and protein levels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Viruses can counteract or enhance the host's sumoylation to evade the immune response and antagonize apoptosis, while some viruses exploit the host's sumoylation machinery to sumoylate the viral components which are necessary to perform viral functions (48). It has been reported that KSHV modulates the SUMO pathway through RTA/ORF50, K-bZIP/K8, and vPK/ORF36 during lytic replication as well as LANA/ORF73 and viral IRF3 (IRF3)/K10.5/LANA-2 during latency (27,35,(49)(50)(51)(52)(53)(54)(55)(56). Our results showed that LANA bound directly to the SENP6 promoter and repressed its activity, inhibiting SENP6 expression at both the RNA and protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…As a SUMO-specific protease, SENP6 is able to deconjugate SUMO2/3, but not SUMO1, from substrates, especially the poly-SUMO chain (40). Additionally, LANA was reported to be sumoylated by both SUMO1 and SUMO2/3 (35). Thus, we hypothesized that SENP6 might reduce LANA by desumoylation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…LANA-1 plays an important role in repressing lytic genes by binding to and repressing the ORF50/RTA promoter (13,14). It was recently found that LANA-1 recruits the host transcriptional repressor KAP1 (Krüppel-associated box [KRAB]-associated protein 1; also known as TRIM28 or TIF1␤), which repressed the ORF50 promoter (15,16). However, the location, mechanism, and dynamics of LANA-1/KAP1 binding to the ORF50 promoter have yet to be investigated.…”
mentioning
confidence: 99%